Development of PLGA-based itraconazole injectable nanospheres for sustained release - Bian X (Dove Medical Press, 2013)
Xiaomei Bian,1 Su Liang,1 Jyothy John,1 Cheng-Hui Hsiao,1 Xin Wei,2 Dong Liang,1 Huan Xie1 1Department of Pharmaceutical Sciences, College of Pharmacy and Health Sciences, 2Department of Chemistry, College of Science and Technology, Texas Southern University, Houston, TX, USA Purpose: Itraconazole (ITZ) is a synthetic triazole antifungal agent, which is widely used for treatment and prevention of fungal infections. The purpose of this study is to develop ITZ-loaded poly(lactic-co-glycolic acid) (PLGA) nanospheres (PLGA-ITZ-NS) as a new sustained-release formulation for intravenous ITZ administration. Materials and methods: PLGA-ITZ-NS were prepared by a nanoprecipitation method and optimized by modifying the surfactant poloxamer 188 concentration and PLGA:ITZ ratio. Their physicochemical properties, including size, zeta potential, external morphology and encapsulation efficiency, were characterized by dynamic light scattering (DLS), scanning electron microscopy (SEM) and high performance liquid chromatography (HPLC). The effect of the different selected lyoprotectants with various concentrations on NS particles size and surface charge were also assessed. Rapid and sensitive HPLC and liquid chromatography-tandem mass spectrometry (LC-MS/MS) methods were developed to determine ITZ concentrations in formulation and in rat plasma, respectively. Pharmacokinetics of the optimum PLGA-ITZ-NS formulation was compared with the former commercial Sporanox® injection formulation using rats as the animal model. Noncompartmental pharmacokinetic parameters were obtained by WinNonlin® software. Results: Optimal PLGA-ITZ-NS had a mean particle size of about 200 nm with a high homogeneity (polydispersity index ≈0.2), favorable zeta potential (approximately -20 to -30 mV) and encapsulation efficiency (72%). In addition, 2% w/v sucrose was selected as a lyoprotectant for NS freeze-drying. The newly developed LC-MS/MS assay was validated and found to be accurate and precise. The in vivo study showed that the NS formulation has a similar systemic bioavailability to Sporanox®while providing a sustained plasma level (>100 ng/mL) for up to 24 hours after intravenous administration. Conclusion: Our newly developed PLGA-ITZ-NS has shown great sustained release and comparable bioavailability with Sporanox®, therefore having the potential to be an alternative injectable formulation of ITZ. Keywords: itraconazole, poly(lactic-co-glycolic acid), PLGA, nanoparticle, sustained release, pharmacokinetics, intravenous injection